Student Responses to the Implementation of the Read-Answer-Discuss-Explain-Crate Learning Model through the Zoom Meeting Application - Sritiawati, Tia; Sopandi, Wahyu; Sujana, Atep; Agustin, Mubiar (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2022)
This study aims to determine student responses to the application of the Read-Answer-Discuss-Explain-Crate learning model through the Zoom Meeting Application. This research uses a descriptive research method and qualitative approach. The subjects of this study were 28 students of class V Elementary School in a private elementary school in the Antapani area. The instrument used is in the form of a questionnaire containing positive and negative statements that students will choose according to what they experienced during learning activities. The data obtained in this study will be analyzed by calculating the percentage results of each statement of student responses to the implementation of the Read-Answer-Discuss-Explain-Crate Learning Model through the Zoom Meeting Application. From the results of the study, it was found that on average more than 75% of students responded positively to the application of the RADEC learning model through the zoom meeting application.